Strategic Dynamics : Concepts and Cases - Burgelman, Robert A, Grove, Andrew S. (Mc Graw Hill, 2006)
This book has its roots in a somewhat unusual pedagogical collaboration: An academic (RAB) and a chief executive officer of a major high-technology company (ASG) getting together to find a way to integrate action-based but reflective executive experience with theory-based but grounded academic research for the purpose of providing a novel learning experience for MBA students.